CRISPR-Cpf1 assisted genome editing of Corynebacterium glutamicum - Yu Jiang (Nature Communications, 2017)
Corynebacterium glutamicum is an important industrial microbe, however it has proven difficult to genetically engineer using Cas9 from Streptococcus pyogenes. Here the authors report effective genome engineering of the bacterium using Cpf1 from Francisella novicida.